Gender considerations in innovation platforms in the livestock sector in Mali - Gning, S.B.; Dione, Michel M.; Sene, M.T.D.; Sow, Ahmadou; Fall, Abdou (Informa UK Limited, 2025)
Innovation platforms (IPs) are spaces for coordination, mutual learning, and consultation among different actors in a value chain to diagnose and solve common problems. They were set up as part of USAID Feed the Future Mali Livestock Scaling Technology Program to address the challenges of the ruminant livestock sector in Mali, including low visibility and weak participation of women in livestock production and marketing. Our purpose in this paper is to report gender considerations in the process of supporting women farmers empowerment embedded in IPs. Qualitative data was collected from project sites over a six-month; 50 iterative interviews were conducted, including 21 in-depth individual interviews, 7 focus groups, 2 participatory workshops and 20 key informant interviews. All interviews were conducted in total with 106 individuals, including 49 men and 14 women livestock farmers. Our results show that the empowerment of women livestock farmers was not systematic with IPs, but rather depends on gender relations and dynamics in the specific social contexts in which these IPs were implemented.